Difficult : mothering challenging adult children through conflict and change - Smith, Judith R. (Clinical social worker) (Rowman & Littlefield, 2022)
"Difficult presents detailed stories of how women balance their desire to protect their challenging adult children alongside feelings of resentment, helplessness, isolation, shame, and fear for their children's future and their own safety"--